Strategi Produk Berbasis Kearifan Lokal - Djuarni, Wenny (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2023)
Product strategy based on local wisdom aims to develop marketing to produce highly competitive products. The sample selected one key informant and fifteen supporting informants, namely owners, employees and consumers of Sari Putra Micro, Small and Medium Enterprises (UMKM). The data used is triangulation technique with observation, interviews and documentation. Fishbone Diagram analysis method with the formulation of the percentage of assessment, verification and conclusions. The results showed that the strategy for Tengteng products based on local wisdom in an effort to develop marketing on product identity brands was 75% and brand rights were 31%, packaging attractiveness was 50%, innovation in product quality was 100%, product variants were 75% and product design was 69%, in product information label 62% and 100% halal certification. The factors that hamper Tengteng's product strategy in an effort to develop marketing are brand rights at 31% and packaging attractiveness at 50% which are categorized as low. The innovations carried out by UMKM Sari Putra on tengteng products by modifying local wisdom on products consisting of local ingredients, local food production processes and local marketing with creativity that are accepted by all market segments. The implementation of a simple product strategy using local marketing, production processes without machines and a lack of human resources, does not yet have brand rights, this is because the product marketing system has been replaced by other manufacturers, so that it has become the sole means of expanding the distribution of Tengteng's products more broadly.